Studi Kelayakan Bisnis Pendirian Bimbingan Belajar Bunda Hajar di Bandung - Nani Juningsih; Patria Supriyoso (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
With the development of the community's economy and changing patterns of life, especially in urban areas where community mobility is quite high, parents' time in guiding and educating their children in terms of education is of course decreasing. This of course makes English tutoring an alternative choice for parents to prepare and improve their children's ability to speak English. The phenomenon mentioned above indicates that the prospects for establishing English language tutoring services are quite large. English is big business. English language skills are important for one's competitiveness. With good English skills, good competitiveness, which is useful for our country too. However, that doesn't mean we have to forget Indonesian, which has become our national language.With these considerations in mind, the author plans to establish a non-formal educational institution in the form of a business, namely in the form of a service company engaged in the field of English language tutoring (tutoring) institutions with the name "Mother Hajar's English Language Tutoring", with an address at Jalan Margaluyu Rt 009, Rw 09, Margasari Village, Buah Batu District, Bandung City, West Java. This non-formal educational institution positions its business as a conversational English center or specializes in English conversation. Based on the analysis of business feasibility studies, this research uses a qualitative descriptive research method, with research objects of business feasibility studies from legal aspects, environmental aspects, market and marketing aspects, technical and technological aspects, human resource aspects, and financial aspects. With observational data collection techniques by means of literature study. The vision is: "To become a reliable and trustworthy English language education institution that can reach all levels of society"